Partition of Anammox and Nitrifiers Through Bio-Carriers for Full-Scale Sidestream Partial Nitrification–Anammox Plant - Xu, Jinliang; Cui, Qingjie; Bu, Cuina; Ismail, Sherif; Ni, Shou-Qing (Frontiers in Bioengineering and Biotechnology, 2022)
To reveal the partition mechanism of anammox and nitrifiers in a full-scale partial nitrification-anammox plant, this study assessed the activity and community structure in different types of sludge. Batch experiments confirmed that suspended sludge had higher partial nitrification capacity, and biofilm sludge had higher anammox activity, 16.9 times higher than suspended sludge. qPCR analysis confirmed that the amoA gene was mainly present in suspended sludge, and highest abundance of Amx gene was observed in biofilm sludge, reaching 1.01×107 copies/ng DNA. High throughput results revealed that Nitrosomonas was the main ammonia oxidizing bacteria with high activity in suspended sludge. And Candidatus Brocadia had the highest abundance of 13.4% in biofilm sludge. This is the exploration of the microbial community of three different sludge types in the full-scale side-stream PN/A system for the first time, which can guide the construction and replication of full-scale PN/A plants.